PRELIMINARY STUDY ON THE REARING OF CHILKA PRAWN("KANTALA ")PENAEUS INDUS H. MILNE -EDWARD IN THE BRACKISH WATER PONDS AT KESHPUR (ORISSA) - MOHANTY, S K (Fishery Technology, 2017)
Results of the experimental rearing of Penaeus indicus withoutsupplemental feeding in the unfertilized brackishwater ponds inthe fore-shore of the Chilka lake are presented in this paper.Higher rate of survival was recorded lin the experiment whereadvanced juveniles were stocked and lower rate of survival wasrecorded where early juveniles were stocked. The averagegrowth rate recorded from the rearing experiments was higherthan the average growth rate of Penaeus indicus recorded fromthe adjoining Chilka lake which indicates the promising futureof prawn farming in and around the Chilka lake. Analysisof gut contents revealed that Penaeus indicus could efficientlyutilise the algal and higher plant matter present in the ponds.No noticeable differences in daily growth rates were noticedbetween early and advanced juveniles in the rearing experiments